Establishment of an in vitro placental barrier model cultured under physiologically relevant oxygen levels. (11th March 2020) - Wong, Michael K; Li, Edward W; Adam, Mohamed; Selvaganapathy, Ponnambalam R; Raha, Sandeep
Abstract: The human placental barrier facilitates many key functions during pregnancy, most notably the exchange of all substances between the mother and fetus. However, preclinical models of the placental barrier often lacked the multiple cell layers, syncytialization of the trophoblast cells and the low oxygen levels that are present within the body. Therefore, we aimed to design and develop an in vitro model of the placental barrier that would reinstate these factors and enable improved investigations of barrier function. BeWo placental trophoblastic cells and human umbilical vein endothelial cells were co-cultured on contralateral sides of an extracellular matrix-coated transwell insert to establish a multilayered barrier. Epidermal growth factor and forskolin led to significantly increased multi-nucleation of the BeWo cell layer and increased biochemical markers of syncytial fusion, for example syncytin-1 and hCGβ. Our in vitro placental barrier possessed size-specific permeability, with 4000-Da molecules experiencing greater transport and a lower apparent permeability coefficient than 70 000-Da molecules. We further demonstrated that the BeWo layer had greater resistance to smaller molecules compared to the endothelial layer. Chronic, physiologically low oxygen exposure (3–8%) increased the expression of hypoxia-inducible factor 1α and syncytin-1, further increased multi-nucleation of the BeWo cell layer and decreased barrier permeability only against smaller molecules (457 Da/4000 Da). In conclusion, we built a novel in vitro co-culture model of the placental barrier that possessed size-specific permeability and could function under physiologically low oxygen levels. Importantly, this will enable future researchers to better study the maternal–fetal transport of nutrients and drugs during pregnancy.